Developments and clinical experiences in collagenase chemonucleolysis for lumbar disc herniation: a narrative review - Zhang, Hao; Zhang, Chi; Li, Lin; Hu, Ming-liang; Zhao, Jian-ning; Zheng, Zhang; Ding, Wen-feng (Frontiers in Medicine, 2025)
Lumbar disc herniation (LDH) affects millions globally, with annual healthcare costs exceeding $100 billion in the United States alone, driving increasing interest in minimally invasive radiological interventions as treatment alternatives. This narrative review examines developments in collagenase chemonucleolysis for LDH, integrating a literature analysis with clinical experience. Key advancements include the transition from single-agent to combination therapies, exploration of diverse injection routes, and the progression from C-arm fluoroscopy to multi-slice CT guidance. The synergistic use of collagenase, oxygen-ozone, and anti-inflammatory analgesics has enhanced efficacy. Safety measures such as aspiration tests, contrast agent tests, and lidocaine tests implemented to mitigate procedural risks. However, challenges persist, including non-standardized dosages and potential complications arising from intradiscal injections. Future research should focus on establishing accreditation systems, refining patient selection criteria, optimizing drug dosages, and exploring advanced image-guided technologies. While chemonucleolysis offers advantages such as minimal invasiveness and cost-effectiveness, its complexity necessitates a multidisciplinary approach. Key findings demonstrate that combination therapy achieves superior outcomes compared to monotherapy, with long-term efficacy rates reaching 90% and 6-month success rates of 95%. Additionally, CT guidance has significantly improved procedural precision and safety compared to traditional fluoroscopy. This review provides insights for clinicians and researchers, highlighting the potential of chemonucleolysis in LDH management to ensure its safe and effective integration into mainstream treatment protocols.